Protein kinase R-like endoplasmic reticulum kinase pathway and diabetic kidney disease - 庞欣欣; 彭紫凝; 邢玉凤; 张雅歌; 石秀杰; 韩佳瑞 (Linchuang shenzangbing zazhi)
Endoplasmic reticulum stress is closely related to the occurrence and development of diabetic kidney disease.As an important signaling pathway induced by endoplasmic reticulum stress,protein kinase R-like endoplasmic reticulum kinase(PERK)pathway can regulate protein synthesis to act as an adaptive response pathway,and protect cells when endoplasmic reticulum stress occurs.However,when endoplasmic reticulum stress is too strong or persistent,PERK pathway can promote cell death by inducing the expression of apoptosis genes.In recent years,studies found that PERK pathway have a close relationship with the pathogenesis of diabetic kidney disease,such as apoptosis,inflammation,oxidative stress,autophagy,angiotensin Ⅱ,etc.This paper reviewed the research progress of PERK pathway in the pathogenesis of diabetic kidney disease and proposed that PERK pathway may be a new target for the treatment of diabetic kidney disease